Dense manganese doped biphasic calcium phosphate for load bearing bone implants - Iis, Sopyan; Ahmad Nawawi, Natasha; Shah, Qasim Hussain (Trans Tech Publications, Switzerland, 2010)
Dense pure biphasic calcium phosphate (BCP) and Mn-doped BCP ceramics were fabricated via uniaxial pressing using the sol-gel derived powders. The compacted discs were sintered in air atmosphere with temperatures ranging from 1000 ºC to 1400 ºC. All powders have been proved to show HA and β-TCP phases only. Manganese doping improves the densification in the BCP structure as the relative density increased with Mn doping and also sintering temperature. Considerable grain growth has been observed at 1300 ºC for Mn-doped BCP samples compared to the pure BCP. 15 mol% Mn showed the maximum hardness value of 6.66 GPa at 1400 ºC compared to pure BCP of only 2.89 GPa. Similarly, the Mn-doped BCP has superior fracture toughness where it attained maximum values of 1.05 MPam1/2 at 1400 ºC compared to 0.72 MPam1/2 at 1300 ºC of pure BCP. In a nutshell, Mn doping has successfully brought improvement in the mechanical properties of the BCP.